Protocol for Dissection and Dissociation of Zebrafish Telencephalon for Single-Cell Sequencing - Cosacak, Mehmet Ilyas (STAR Protoc, 2020)
Single-cell sequencing (sc-Seq) is a powerful tool to investigate the molecular signatures of cell types in a complex mixture of cells. A critical step in sc-Seq is preparing a single-cell suspension with a high number of viable cells. Here, we show how to dissect zebrafish telencephalon and how to dissociate it into a single-cell suspension. This is followed by flow cytometry-based sorting to enrich for neural progenitor stem cells. Our technique typically yields 70,000 live cells from one zebrafish telencephalon. For complete details on the use and execution of this protocol, please refer to Cosacak et al. (2019).